Analysis Family Assistance by Health Cadres Can Increase LILA of Pregnant Women - Nurhalinah Nurhalinah; Ari Athiutama (Syntax Corporation Indonesia, 2024)
One of the problems caused by malnutrition in pregnant women is Chronic Energy Deficiency (CED). CED is a condition where a mother experiences a chronic (chronic) lack of energy and protein. Efforts made to improve the nutrition of pregnant women with KEK are by providing additional food). Objective: to determine the effect of giving local food, (local, local food: eg; catfish, catfish, vegetable Sutan and local fruit) on changes in LILA in KEK pregnant women. Method: The research used a quasi-experimental design. The research was conducted in November 2023–January 2024. The sample size was calculated using the Lameshow formula and a sample of 22 people was obtained, with a total of 26 people in each group. Research was carried out by interviews and observations. Bivarate data analysis used the non-parametric Mann-Whitney test. Results: The results of the study showed that there was a difference in LILA in the control and treatment groups (P=0.000). Conclusion: there are differences in hemoglobin and LILA in the control and treatment groups.